Faktor-Faktor Produksi yang Berpengaruh dalam Usahatani Cengkeh di Desa Puulemo Kecamatan Lembo Kabupaten Konawe Utara - Sari, Firdach Nopita; Bafadal, Azhar; Yusria, Wa Ode (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2017)
This study aims to determine the influence of clove farming production factors in the village of Puulemo Kecamatan Lembo District Konawe Utara. The data collected in this study is using primary data and secondary data primary data obtained from direct interviews with farmers by using questionnaires. The sampling method is simple random sampling, with the number of farmers as many as 60 samples. The analysis used in this study is to use Cobb-Douglas function analysis to make it easier to make guesses then the equation is converted into a linear form. Independent variable of labor, fertilizer and per hectare land area The results showed that labor variable (X1) and fertilizer (X2) together and significantly effect on clove production in Puulemo Village Kecamataan Lembo regency of Konawe Utara at a level of Î± =0,05